Fine-mapping of prostate cancer susceptibility loci in a large meta-analysis identifies candidate causal variants - Tokhir Dadaev (Nature Portfolio, 2018)
Prostate cancer (PrCa) involves a large heritable genetic component. Here, the authors perform multivariate fine-mapping of known PrCa GWAS loci, identifying variants enriched for biological function, explaining more familial relative risk, and with potential application in clinical risk profiling.